Conocimiento sobre el virus del papiloma humano y el cáncer cérvicouterino en los estudiantes del colegio presidente Isidro Ayora del Barrio Plateado - Chamba Tamay, Liliana Jakeline (2015)
The Human Papillomavirus (HPV) is a disease with high incidence worldwide, mainly being caused by strains 16 and 18 sexually contract through minimal erosions of the skin and mucous membranes. The cervix is especially vulnerable to infection, likely through the epithelium of the squamocolumnar junction. HPV has a very important role in cancer of the anus, vulva, vagina, penis and produces epithelial benign growths such as warts, papilloma and condyloma. Normally the infection remains latent and according to chronicity, can produce malignant tumors in the cervix or penis The prevalence of HPV infection in asymptomatic women, varies between 2 and 44%. The prevalence of HR-HPV in the general population correlates very well with the incidence rates of cervical cancer in all regions of the world .Being so the Ecuador sits in eighth place in the countries of South America infection. The research was quantitative, had as general objective: To determine knowledge about the Human Papillomavirus and Cervical Cancer in college students "President Isidro Ayora neighborhood of Silver" the same as was done during the period 2014-2015. The technique used was the survey instrument and the questionnaire answer choice questions related to the research topic. The research is socially relevant because it could help improve strategies to reduce the incidence of these STIs in the population, helping to propose educational programs and delivery of materials for the promotion of health from educational institutions, raising awareness in the population from Youth ages. Keywords: Knowledge, papilloma virus and cervical cancer.